Iron Deficiency Anemia in Inflammatory Bowel Disease: What Do We Know? - Resál, Tamás; Farkas, Klaudia; Molnár, Tamás (Frontiers in Medicine, 2021)
One of the most common extraintestinal manifestations of inflammatory bowel disease is iron deficiency anemia. It is often an untreated condition that significantly impairs patients' quality of life and elevates mortality and morbidity. Although it is often accompanied by mild symptoms (e.g., fatigue, lethargy), it can provoke severe health conditions, such as dyspnea, palpitation, angina, and mental disorders, and increases hospitalization and mortality rate as well. As anemia develops through several pathomechanisms, such as occult bleeding, chronic inflammation, and medicines (e.g., methotrexate), treating anemia effectively requires to manage the underlying pathological changes as well. Based on international publications and data, it is a frequent condition and more frequent in pediatrics. According to Goodhand et al., iron deficiency is present in more than 60% of children, whereas only 14% of them received oral iron therapy. Compared to adult patients, 22% have iron deficiency, and 48% of them received oral and 41% intravenous iron therapy. Miller et al. also highlighted that among young patients iron deficiency anemia is a frequent condition, as almost 50% of the patients were anemic in their cohort. European Crohn's and Colitis Organisation's statements are clear regarding the diagnosis of iron deficiency anemia, and the iron supplementation as well. Third-generation parenteral iron supplementations seem to be safer and more effective than oral iron pills. Oral iron in many cases cannot replace the iron homeostasis as well; furthermore, it can provoke dysbiosis, which can potentially lead to relapse. As a result, we claim that both oral and parenteral should be used more frequently; furthermore, intravenous iron could replace oral medicines as well in certain cases. Despite the fact that iron deficiency anemia is examined by many aspects, further questions can be raised. Can it imply underlying pathological lesions? Are both oral and intravenous iron therapy safe and effective? When and how are they used? We demand that more studies should be conducted regarding these issues.